Improving Islamic Senior High School Students’ Speaking Skills Through the Debate Method - Lisa Novita Sari; Sultan Baa; Nur Aeni (Journal of Excellence in English Language Education, 2026)
This investigation explores the role of the Structured Classroom Debate method in elevating speaking proficiency among students at MAN 4 Bone. Adopting a quantitative pre-experimental design, specifically a one-group pretest-posttest model, the study involved 30 tenth-grade participants. Speaking was evaluated through an oral assessment rubric focusing on fluency, pronunciation, grammar, vocabulary, and argument coherence. Post-intervention analysis demonstrated substantial gains, with mean scores climbing from 42.66 (pretest) to 90.13 (posttest). The N-Gain score reached 0.84, categorized as high effectiveness. A paired samples t-test produced a significance level below 0.001, affirming the statistical validity of the improvements. Notably, every speaking component advanced, with fluency exhibiting the most dramatic increase, followed sequentially by vocabulary, pronunciation, argument clarity, and grammar. These outcomes indicate that debate activities foster greater oral engagement, refined idea structuring, and heightened delivery confidence. Consequently, the Structured Classroom Debate emerges as a highly suitable and impactful technique for advancing speaking abilities in educational settings.